State Budget Crises and Access to College for Undocumented Students in the United States - Fanny Lauby (Revue LISA)
The financial crisis has intensified the concerns over the availability of financial aid for all students in the public higher education system of the United States. Even in better economic times, financial aid and access to in-state tuition often determine whether or not a student is going to attend college. This is all the more relevant for minority and low-income students, among whom are some undocumented immigrants. This paper examines the relationship between the 2007-2008 financial crisis and state laws related to undocumented students’ access to in-state tuition and financial aid. Along with the rest of the unauthorized population living in the United States, these youths now have to face a serious backlash from state legislatures claiming to cut costs for their own government. Despite a recent ruling by the California Supreme Court favorable to in-state tuition for undocumented students, several state legislatures have enacted policies which will marginalize them even further. The crisis has in fact toughened the relationship existing between state government and public institutions of higher education. The article shows that the economic downturn has accelerated the change in the role of public universities, and especially their exploitation by state legislatures in their opposition to undocumented immigration.